2021
DOI: 10.7554/elife.59350
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus restricts ICOSL expression on antigen-presenting cells disabling T cell co-stimulation and contributing to immune evasion

Abstract: Viral infections are controlled, and very often cleared, by activated T lymphocytes. The inducible co-stimulator (ICOS) mediates its functions by binding to its ligand ICOSL, enhancing T-cell activation and optimal germinal center (GC) formation. Here, we show that ICOSL is heavily downmodulated during infection of antigen-presenting cells by different herpesviruses. We found that, in murine cytomegalovirus (MCMV), the immunoevasin m138/fcr-1 physically interacts with ICOSL, impeding its maturation and promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Conversely, T cell costimulation was more prevalent in the low-risk group. This could be because cytomegalovirus in the high-risk group inhibits ICOSL transcription on antigen-presenting cells, inhibiting T lymphocyte costimulation, thereby resulting in immunological resistance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, T cell costimulation was more prevalent in the low-risk group. This could be because cytomegalovirus in the high-risk group inhibits ICOSL transcription on antigen-presenting cells, inhibiting T lymphocyte costimulation, thereby resulting in immunological resistance [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated T cells express ICOS on their surface, which enhances the ability of T cells to secrete cytokines after binding to ICOSL on the surface of cells, such as B cells, DC, and macrophages 23,24 . Our results show that activated Vγ9Vδ2 T cells also express ICOS on its surface (Figure 7B,E) and ICOSL on the MDSC surface of the same individual (Figure 7C,F), but the result of neutralizing ICOSL is disappointed (Figure 7J–L).…”
Section: Discussionmentioning
confidence: 75%
“…However, the addition of immune checkpoint mixed neutralizing antibodies has no significant effect on the ability of MDSC to downregulate NKG2D expression and upregulate the produce of CD107a, IFN-γ, perforin, and Granzyme B in Vγ9Vδ2 T cells (Figures1F, 2-4B-D, and 5B). This further confirms that the effect of MDSC in downregulating NKG2D in Vγ9Vδ2 T cells is only related to its membrane-type TGF-β, and confirms that MDSC has the ability to up-regulate the synthesis and secretion of IFN-γ, perforin, and Granzyme B by Vγ9Vδ2 T cells.Activated T cells express ICOS on their surface, which enhances the ability of T cells to secrete cytokines after binding to ICOSL on the surface of cells, such as B cells, DC, and macrophages 23,24. Our results show that activated Vγ9Vδ2 T cells also express ICOS on its surface (Figure7B,E) and ICOSL on the MDSC surface of the same individual (Figure7C,F), but the result of neutralizing ICOSL is disappointed (Figure7J-L).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Low expression of MHC-II molecules can also lead to the occurrence of immune escape due to the inability to effectively activate T cells (Zhi et al, 2021). In addition, the activation of T cells also requires the participation of costimulatory molecules (Angulo et al, 2021). We found that MHC-I molecules, MHC-II molecules, and costimulatory molecules, which are associated with endogenous immune escape, were all low expressed in the high-risk group.…”
Section: Discussionmentioning
confidence: 77%